How to transversely develop ability emotional intelligence ability through school subjects? : A theoretical proposal - Mestre, José M. (Array, 2020)
Since emotional intelligence (EI) was developed in 1990, the field of Education took advantage of the possibilities of EI. Indeed, EI-specific programs proliferated and developed as socio-emotional learning programs (SEL). However, there is an alternative to realize non-specifically and longer and viability way for improving the implicit abilities of EI (AEI). The article claims to work a theoretical proposal to develop the AEI in compulsory education through the subjects. This proposal is based on the Cattell-Horn-Carroll theory of cognitive abilities (CHC). CHC abilities are stimulated by most of the mandatory subjects of both Primary and Secondary Schools. The second stratum of CHC model is composed of similar cognitive abilities as 1997-Ability Emotional Intelligence Model (perception, using, understanding, and managing emotions), which is different from trait EI approaches - that consider EI has personality traits as well. It has pointed out that the capacities of the CHC-model second stratum are connected to the capabilities of AEI. Therefore, any educational activity that optimizes perception, understanding, attentional control or planning is affecting the development of AEI. Promoting AEI involves hot information processing. It is convenient to use transversely hot information processing - this means that this information has special meaning for the people. Connecting hot information to mandatory subjects teaching would develop the abilities of EI. Both Sciences and Natural Sciences pedagogic devices can improve emotional perception. However, Social Sciences and Humanities foster both emotional understanding and knowledge. Finally, the different contingencies that occur in school life scenarios are suitable for training of emotional regulation.